Profit Sharing and Workplace Productivity: Does Teamwork Play a Role? - Richard J. Long; Tony Fang (Institute for the Study of Labor (IZA), 2013)
The conditions under which profit sharing affects workplace productivity have never been fully understood. Using panel data, this paper examines whether there is any link between adoption of an employee profit sharing plan and subsequent productivity growth in Canadian establishments, and whether this relationship is affected by various contextual factors, particularly use of work teams. In so doing, we use both three and five-year panels. Overall, we find a significant link between adoption of a profit sharing program and subsequent productivity growth in both panels, but only among establishments that utilize employee work teams.
Keywords: J33; J24; J54; 330; profit sharing plans; workplace productivity; teamwork; firm-worker linked survey; Canada